Social networks and online communities in the educational context - Márquez Moncada, Catalina María (2017)
Social networks and online communities are connection and interaction spaces between people that the use of the internet has generated. These virtual spaces can be used in the educational context and transform teachinglearning processes as spaces for communication and socialization, especially considering that the role of the teacher and student has also been transformed by this context.